Deciphering the role of CNIH4 in pan-cancer landscapes and its significance in breast cancer progression - Xu, Yao; Lai, Zengzhen; Li, Chaolin (Frontiers in Genetics, 2025)
BackgroundThe escalating global cancer burden necessitates the development of biomarkers with enhanced specificity and sensitivity for early diagnosis and therapeutic efficacy monitoring. The CNIH4 gene, an emerging biomarker, is increasingly recognized for its role in the malignant progression across various cancers.MethodsWe conducted a comprehensive multi-omics analysis of CNIH4, including pan-cancer expression profiles, epigenetic alterations, immune microenvironment characteristics, and therapeutic response patterns. Our focus was on clinical features, molecular underpinnings, and drug sensitivity in breast cancer (BRCA) associated with CNIH4. In vitro studies were also performed to assess the effects of CNIH4 knockdown on cell proliferation and cell cycle in the MDA-MB-231 cell line.ResultsCNIH4 upregulation was observed in multiple cancers, significantly correlating with genomic instability. High CNIH4 expression levels were linked to poor prognosis across cancers and associated with key cancer-related pathways, particularly those in cell cycle regulation and DNA repair. Correlation analyses suggest a role for CNIH4 in the tumor immune microenvironment, as evidenced by its association with immune subtypes, immune-related genes, and immune cell infiltration. Single-cell and spatial transcriptome analyses confirmed that CNIH4 expression in BRCA predicts tumor malignancy. Drug sensitivity analysis revealed a significant correlation between CNIH4 and responsiveness to various kinase inhibitors and chemotherapeutic agents. In vitro experiments demonstrated that CNIH4 knockdown significantly impacts the proliferation and cell cycle of MDA-MB-231 cells.ConclusionOur study highlights CNIH4 as a promising pan-cancer biomarker with significant implications for tumor progression and a critical role in cell cycle regulation in BRCA.